2018
DOI: 10.1038/s41419-018-0267-9
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine receptor CCR10 promotes inflammation-driven hepatocarcinogenesis via PI3K/Akt pathway activation

Abstract: G-protein-coupled receptor (GPCR)-related proteins are dysregulated and the GPCR CC-chemokine receptor 10 (CCR10) is significantly upregulated in inflammation-driven HCC. However, CCR10′s role in inflammation-driven hepatocarcinogenesis remains unknown. The aim of this study was to evaluate the role of CCR10 in inflammation-driven hepatocarcinogenesis. Via a targeted gene expression microarray screening alterations in GPCR family gene expression, we found CCR10 to be significantly upregulated in hepatocytes is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 33 publications
3
42
0
Order By: Relevance
“…Recently, researches demonstrated that chemokines and their receptors play a critical role in tumor cell growth and metastasis in melanoma, lung cancer, gastric carcinoma, pancreatic cancer, colorectal carcinoma and hepatocellular carcinoma [28]. It has been reported that CCR10 activation stimulates the progression, invasion and migration of HCC, breast cancer cells and melanoma cells [11,29,30]. CCR10 expression and downstream PI3K/Akt pathway shows a role in HCC progression [11].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, researches demonstrated that chemokines and their receptors play a critical role in tumor cell growth and metastasis in melanoma, lung cancer, gastric carcinoma, pancreatic cancer, colorectal carcinoma and hepatocellular carcinoma [28]. It has been reported that CCR10 activation stimulates the progression, invasion and migration of HCC, breast cancer cells and melanoma cells [11,29,30]. CCR10 expression and downstream PI3K/Akt pathway shows a role in HCC progression [11].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the PI3K/Akt/GSK-3β signaling and the transcriptional repressor Snail were required for EMT of HCC [9,11]. Activated downstream molecules of PI3K/Akt/GSK-3β could mediate the stabilization of endogenous Snail.…”
Section: Plasmodium Infection Suppressed the Activation Of Pi3k/akt/gmentioning
confidence: 95%
See 3 more Smart Citations